"Eurowhite Conceit, " "Dirty White" Ressentiment: "Race" in Europe by József Böröcz: A Comment. Issue 1 (3rd January 2022) - Lentin, Alana
Abstract : This essay is written in response to Böröcz's (2021) essay on race in Europe.